Media Pembelajaran Masa Kini: Aplikasi Pembuatan dan Kegunaannya - Rohmah, Nafilatur (Awwaliyah: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2021)
The development of learning media changes along with technological developments. Technological advances can be used by teachers to create creative and innovative learning media. Applications for making learning media include: (1) Cup Cut and Kinemaster for making audio-visual learning media; (2) Kahoot, Quizizz, Educandy, Wordwall, Academy Khan Kids, and Boombazle for educational games; (3) Powtoon and animaker applications for making animation learning media.